Simultaneous convergence of position and orientation of wheeled mobile robots using trajectory planning and robust controllers. (7th February 2018) - Becerra, Héctor M; Colunga, J Armando; Romero, Jose Guadalupe
This article is devoted to the design of robust position-tracking controllers for a perturbed wheeled mobile robot. We address the final objective of pose-regulation in a predefined time, which means that the robot position and orientation must reach desired final values simultaneously in a user-defined time. To do so, we propose the robust tracking of adequate trajectories for position coordinates, enforcing that the robot's heading evolves tangent to the position trajectory and consequently the robot reaches a desired orientation. The robust tracking is achieved by a proportional–integral action or by a super-twisting sliding mode control. The main contribution of this article is a kinematic control approach for pose-regulation of wheeled mobile robots in which the orientation angle is not directly controlled in the closed-loop, which simplifies the structure of the control system with respect to existing approaches. An offline trajectory planning method based on parabolic and cubic curves is proposed and integrated with robust controllers to achieve good accuracy in the final values of position and orientation. The novelty in the trajectory planning is the generation of a set of candidate trajectories and the selection of one of them that favors the correction of the robot's final orientation. Realistic simulations and experiments using a real robot show the good performance of the proposed scheme even in the presence of strong disturbances.